Alteration Index Three Facilitates Interpretation of β-Glucosidase, Acid-phosphatase and Urease Activities in Soils Irrigated with Diluted Winery Wastewater - van Huyssteen, I.; Mulidzi, A.R.; Meyer, A.H.; Wooldridge, J. (South African Journal of Enology and Viticulture, 2020)
Soil enzyme activity data from a lysimeter pot trial involving four dissimilar soils irrigated over two simulated seasons (SS) with winery wastewater (WW) and municipal water (MW), were converted to numerical scores using the alteration index three (AI3). Unlike the activities of individual enzymes which are substrate specific and do not reflect the overall status of the soil microbiome, AI3 enabled differences in treatment-induced alteration states between combinations of soil and water to be quantified and statistically assessed. The more negative AI3 scores corresponded to a more altered state in the WW than the MW treatments, after SS3 than after SS4 and in the 0-10 cm compared to the 10-20 cm soil depth interval. AI3 is therefore a potentially useful adjunct to soil enzyme activity assays in monitoring and management of biological activity in vineyard soils. These findings, however, require verification under commercial vineyard conditions.